RANCANG BANGUN GAMIFIKASI MULTIMEDIA PEMBELAJARAN PADA MATA PELAJARAN PEMOGRAMAN DASAR - Muhammad Ilham Nurfauzan, - (2019)
Generally learning in vocational schools will be more dominated by practical activities rather than the delivery of material in the classroom, so the provision of a solid foundation of understanding of material in schools is less fulfilled. This is caused by the limited availability and completeness of supporting media so students have difficulty in understanding the subject matter. The lack of supporting media used by the teacher in the learning process results in students having difficulty understanding the material. This study aims to produce learning gamification to find out how much influence its use has on increasing students 'understanding of basic programming subjects, as well as to determine students' responses to the learning gamification built. The research subjects were students of class XI RPL SMKN 2 Bandung. The making of this learning gamification is motivated by a lack of understanding in basic programming subjects and a lack of use of the media in the learning process. Based on that problem, its needed a media that helps students in learning basic programming. Games have a fun nature that makes students who are in their teens like it and still often play it. Learning by using games makes students will actively see and do learning compared to listening or reading. Gamification can be an effective alternative to increase student understanding. The multimedia development method used is the Comprehensive Life Cycle (SHM) model. The results of this study are: 1) gamification of learning in basic programming subjects that are built is feasible to use based on the results of expert validation with an average acquisition of 85.58%. Can be classified in the category of "Very Good", 2) gamification of learning in basic programming subjects can improve understanding of concepts, this is seen from the normalized gain value <g> of 0.55 which is categorized in its effectiveness criteria while its effect on learning, and 3) Student responses to the learning gamification were categorized well with an average acquisition of 94.15%.